COVID-19 symptoms, internet information seeking, and stigma influence post-lockdown health anxiety - Li, Qian; Yang, Xue; Wang, Xin; Zhang, Han; Ding, Ningning; Zhao, Wenqian; Tian, Wenwen; He, Jiankang; Du, Mingxuan; Hu, Haiyan; Zhang, Guohua (Frontiers in Psychology, 2023)
Background With the lifting of Zero-COVID policies in China, rapid transmission of the virus has led to new challenges for patients’ health anxiety. This study aimed to evaluate the relationship between COVID-19 symptoms and health anxiety, as well as the mediation paths between them in individuals infected with COVID-19. Method A cross-sectional study was conducted in December 2022, following the relaxation of anti-COVID measures in China. A validated online questionnaire was used to collect data from COVID-19 patients on the number and severity of symptoms, health anxiety, internet health information-seeking behavior (IHISB), and perceived stigma. Structural equation modeling was used to examine the mediation model in which COVID-19 symptoms would affect health anxiety via IHISB and perceived stigma. Results Overall, 1,132 participants (women, 67.6%) were included, with a mean (SD) age of 28.12 (10.07) years. Participants had an average of seven COVID-19 symptoms, with cough (91.3%), nasal congestion (89.1%) and fatigue (87.8%) being the most common. The number and severity of COVID-19 symptoms, IHISB, perceived stigma, and health anxiety were positively correlated with each other after adjusting for covariates (r ranging from 0.10 to 0.81, all p < 0.05). IHISB (effect = 0.14, p < 0.001) and perceived stigma (effect = 0.04, p < 0.001) fully mediated the relationship between COVID-19 symptoms and health anxiety. Conclusion Interventions for health anxiety reduction during and after pandemics should target improving the quality of online health information, enhancing individuals’ online healthy literacy, and reducing stigma.